2016
DOI: 10.1063/1.4971836
|View full text |Cite
|
Sign up to set email alerts
|

Absolute distance measurement method without a non-measurable range and directional ambiguity based on the spectral-domain interferometer using the optical comb of the femtosecond pulse laser

Abstract: Absolute distance measurement method without a non-measurable range and directional ambiguity based on the spectraldomain interferometer using the optical comb of the femtosecond pulse laser Cite as: Appl. Phys. Lett. 109, 244103 (2016); https://doi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In an effort to eliminate these NMR, several preceding studies have employed supplementary methods, including the synthetic wavelength interferometer proposed by Joo et al, 20 the dual-frequency phase modulated laser range finder (PLR) introduced by Wang et al, 5 the multiple-wavelength interferometer presented by van den Berg et al, 21 and the adoption of two reference mirrors as suggested by Kim et al 26 While these methods have been successful in extending measurement distance, they necessitate the support of intricate systems or redundant algorithms. Moreover, they fall short of completely resolving the inherent limitations present in DPI.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to eliminate these NMR, several preceding studies have employed supplementary methods, including the synthetic wavelength interferometer proposed by Joo et al, 20 the dual-frequency phase modulated laser range finder (PLR) introduced by Wang et al, 5 the multiple-wavelength interferometer presented by van den Berg et al, 21 and the adoption of two reference mirrors as suggested by Kim et al 26 While these methods have been successful in extending measurement distance, they necessitate the support of intricate systems or redundant algorithms. Moreover, they fall short of completely resolving the inherent limitations present in DPI.…”
Section: Introductionmentioning
confidence: 99%
“…Such an intrinsic limitation means that the laser interferometer cannot be widely exploited for newly emerging applications, especially for long distances. As a counterpart to laser displacement interferometry, absolute distance measurements have been proposed and realized by various approaches [6,7], including the time-of-flight method [8,9], amplitude modulation ranging [10][11][12][13][14], frequency modulation ranging [15][16][17], spectral resolved interferometry [18][19][20], multi-wavelength interferometry [21][22][23], dual-comb ranging [24][25][26], and microcomb ranging [27][28][29]. One of these examples is LIDAR (light detection and ranging), which works with the time-offlight method [30].…”
Section: Introductionmentioning
confidence: 99%